A ANALISIS PERILAKU KEUANGAN MAHASISWA RANTAU PROGRAM STUDI PENDIDIKAN EKONOMI UNIVERSITAS PENDIDIKAN INDONESIA - Mohammad ilham Ramdani; Anissa Nurfathonah; Arisa Oktaviana Maharani; Naila Zahra Fatinnia; Buyung Firmansyah (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
A research named "Analysis of Financial Behaviour of Overseas Students, Economic Education Study Programme, Indonesian Education University" aims to examine the spending patterns of international students who put their desires before their necessities. Using a quantitative approach, this study describes the experiences of international students at Indonesian Education University's Economic Education programme. Students living in boarding homes or unaccompanied minors from outside the Bandung area are its intended recipients. In order to gather data, 62 students from the 2022 and 2023 cohorts of Economic Education were chosen at random from a pool of potential respondents. The survey, which looked at four markers of financial behaviour (account ownership, cash flow management, spending planning, and saving and investing behaviours), was carried out in April 2024.To determine how well the obtained data matched the specified indicators, descriptive statistics were used in the data analysis process. Overseas students enrolled in the Economic Education programme show signs of having intermediate financial behaviour skills, which might mean they're having trouble keeping their day-to-day money in order. The study's overarching goal is to provide these students with a framework for better managing their money.